Novel and society, a sociohistorical study - messili, taher (El Omda in Linguistics and Discourse Analysis, 2025)
This paper aims at revealing the extent to which a novel is related to the social reality, through following the path of its appearance and development, from the works of the westerners who were the pioneers of it, to those of the Arabs. The study came to a result that a novel is only a mirror of the societies that it depicts in the artistic style, using its own tools in narrating.